Mobility, mobilization, and counter/insurgency: the routes of terror in an African context - Agbiboa, Daniel E. (University of Michigan Press, 2022)
Introduction: The Neglected Linkages between Mobility and Insurgency. – 1. One Dangerous Work(ers): Youth, Motorcycles, and Stuckedness in Nigeria. – 2. Local Immobility and Mobilization into Boko Haram. – 3. The Motorcycle Helmet Law and the July 2009 Violence. – 4. Mobile Warfare, Abuses by Security Forces, and Civilian Resistance. – 5. Subversive Mobilities, State Counterinsurgency, and the Politics of Dispossession. - Conclusion: Toward a Mobile Logic of Insurgency and Counterinsurgency